Model Strategi Prospektif Kinerja Manajemen di Perusahaan Tour & Travel - Aryanto, Rudy; Yuniarty, Yuniarty (Binus Business Review, 2010)
This study aimed to build a prospective management model of sustainable tour packages in PT. GoldenÂ Rama Express. Given the complexity and the many interrelated factors in the performance management package tours, it is necessary to approach a holistic system. First, the method used in developing the performanceÂ management model is a sustainable package tour and, second, using prospective analysis. Determination of theÂ attributes that reflect the sustainability performance of the tour package is based on field studies. Based on theÂ four dimensions of sustainability, namely the dimensions before the trip, during trip, etc., and the tour leader are determined as much as 23 attributes. Attributes in four dimensions for each package tour Junglelicious Africa,Â Asia Splendid, Adventurous Australia and New Zealand, Europe Romantical and Marvelous the U.S. andÂ Canada. After obtained the level of sustainability index values of each dimension that can be categorized into theÂ not sustainable until very sustainable values of the index, combination of these factors forms the basis ofÂ development models.. Based on the scenario that was built and in order to achieve the ideal scenario is theÂ recommended scenario is the optimistic scenario.